Convection enhanced delivery of tri-block copolymer nano-micelles: a method of direct intraparenchymal water-insoluble drug delivery for the treatment of high-grade glioma. (31st January 2018) - Singleton, Will; Collins, Andy; Bienemann, Ali; Killick-Cole, Clare; Asby, Daniel; Haynes, Harry; Wyatt, Marcella; Boulter, Lisa; Gill, Steven
Abstract: Convection enhanced delivery (CED) is a novel neurosurgical method of direct intraparenchymal drug delivery that utilises surgically implanted microcatheters to bypass the blood brain barrier. Drug is infused with the aim to displace the extracellular fluid within a specific volume of brain or tumour and replace it with infusate. In order to enable this, a compound must be water soluble. Many novel targeted compounds that may be useful in glioma treatment do not cross the blood brain barrier and are water insoluble. We describe the use of the triblock co-polymer Poloxamer-407 (P407) in a self-assembling nano-micellar formulation as a vehicle for administering the water insoluble HDAC inhibitor panobinostat for the treatment of high-grade glioma. Drug-loaded P407 micelles were synthesised in artificial CSF using an emulsion-evaporation technique and characterised with dynamic light scattering, zeta potential measurement and 1H Diffusion Ordered Nuclear Magnetic Resonance Spectroscopy. Nano-micelle distribution in rat brain was analysed following acute CED using rhodamine-labelled micelles and toxicity assayed using immunofluorescent microscopy and synaptophysin ELISA. We compared the survival of the bioluminescent syngenic F98/Fischer344 rat glioblastoma model treated by acute CED of panobinostat-loaded nano-micelles, compared to untreated and vehicle-only treated controls. Drug loaded P407 nano-micelles had a mean diameter of 23 nM. CED of fluorescent rhodamine-labelled nano-micelles distribute with a volume of infusion/volume of diffusion (Vi:Vd) ratio of four and five in rat gray and white matter respectively, and was not associated with any toxicity when compared to controls. CED of panobinostat-loaded nano-micelles was associated with significantly improved survival when compared to controls (n=8 per group; Log Rank p<0.001). CED of P407 nano-micelles is a novel method of CNS delivery of water insoluble compounds. CED of nano-micellar panobinostat represents a novel therapeutic option for high-grade glioma therapy and warrants translation into the clinic.